(untitled) (Journal of Dissability Studies and Research (JDSR), 2023)
This journal contains about disability issues on music lyric. In a past, the musicians offered the love-hate issues. But in two decades, the issues more variety, particularly disabbility issues. Literature review is a method that used in this research. The results of this study gives overview how important the external motivation through music, at least disabilities feel accepted in public. The role of government also important to support musicians. It posibble to reach out more dissabilities. Keywords: Songwriting, Disability Music, Manusia Kuat, Jangan Menyerah , Sama Rapuhnya